Integrative medicine selects best practice from public health and biomedicine - Terence J Ryan (Wolters Kluwer Medknow Publications, 2013)
The meaning of terms Integrated and Integrative are described variously by an amalgam of latest scientific advances with ancient healing systems, of complementary medicine and biomedicine, and sexually transmitted infections and HIV/AIDS. It means seamless good quality care between hospital and primary care. They provoke approval mostly from patients and disapproval mostly from advocates of science and evidence-based medicine. The Institute of Applied Dermatology in Kasaragod, Kerala, India has championed a mix of Biomedicine, Yoga and herbals from Ayurvedic medicine, partly based on publications from the Department of Dermatology of the University of Oxford. In Oxford dermatology, acceptance of value of integrative medicine (IM) is demonstrated, especially in wound healing and the skin's blood supply. This has long featured in the university's research program. A variety of approaches to the practice of medicine are illustrated with reference to Osler, Garrod, and Doll. IM is believed to underlie contemporarily best practice. Particular emphasis is given to the control of heat, pain, redness, and swelling, all manifestations of inflammation, and the importance of emotion as a stimulus or inhibitor carried by neural pathways. These may explain some unbelievable Asian practices and one of the many roles of Yoga. The concept of Integrative is expanded to include care of the earth and nutrition, the hazards of climate change, Gardens for Health, do (k) no (w) harm as a key to good practice.